2014
DOI: 10.35808/ersj/414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Freight Transport Time Changes on The Performance of Manufacturing Companies

Abstract: Freight Transport Time (FTT) is an important resource for manufacturing companies, firstly as a cost driver of logistics processes and secondly as a key factor of customer satisfaction. Yet, there is a lot of controversy between researchers regarding the strength of the link between changes in transport time and business performance and the methods used to measure this effect. In this context, the aim of this paper is to estimate the effect that changes in freight transport time have on the economic performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The importance of the role of professional accountants in business in ensuring the quality of financial reporting cannot overly emphasized. Because numerous microeconomic factors have already been identified and said to be operating directly on firms, hence affecting productivity (Sambracos and Ramfu, 2014). In such a situation, professional accountants in business often find themselves being at the frontline of safeguarding the integrity of financial reporting (Jui and Wong, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the role of professional accountants in business in ensuring the quality of financial reporting cannot overly emphasized. Because numerous microeconomic factors have already been identified and said to be operating directly on firms, hence affecting productivity (Sambracos and Ramfu, 2014). In such a situation, professional accountants in business often find themselves being at the frontline of safeguarding the integrity of financial reporting (Jui and Wong, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The development of European logistics was strongly conditioned by the ongoing Cold War and military logistics concepts that were implemented in Western European countries as part of the NATO Pact and the Eastern Bloc. The conceptual basis of Communist Logistics drew on planning the links between military logistics and the national economy, including the use of civil resources, such as trade, industrial production, labour resources, and capital (Young, 2016;Sambracos and Ramfou, 2014). Once the Eastern Bloc collapsed and its countries departed from the central planning policy, some countries, like Poland, were incorporated into NATO structures.…”
Section: Development Trends In European Logisticsmentioning
confidence: 99%
“…Forslund (2007) described modern methods of logistics management and revealed the existence of the relationship between the logistics performance management and the expected results of logistics for customers. Countries with low logistics efficiency indicators face high costs not only because of transportation costs, but also because of unreliable supplies and incorrect measurement (Gogoneata, 2008;Sambracos and Ramfou, 2014). The results of the study using econometric methods and the logistics efficiency index calculated by the World Bank showed that there is a strong relationship between the service sector development and the results of logistics in the country.…”
Section: Literature Reviewmentioning
confidence: 99%